LOGOTHERAPY COUNSELING ENCOUNTER WITH ZAKAT - Rahman, Deni; Hidayat, Rahmad; Silvianetri, Silvianetri; Irman, Irman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to examine the relationship between logotherapy counseling and zakat. This research uses library research. The data used in this research is secondary data obtained from books, journals and scientific articles. The research results show that logotherapy and zakat counseling have a high level of agreement. The meeting between counseling perspective of logotherapy with zakat can be seen from three aspects, namely aspects goals aspects values and aspects of the process, so the meeting between zakat and logotherapy perspective counseling can help clients to live a more meaningful and useful life